2014
DOI: 10.1155/2014/450423
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Enteric Viruses in Production Chickens Is a Concern for Avian Health

Abstract: Several viruses have been identified in recent years in the intestinal contents of chickens and turkeys with enteric problems, which have been observed in commercial farms worldwide, including Brazil. Molecular detection of these viruses in Brazil can transform to a big threat for poultry production due to risk for intestinal integrity. This disease is characterized by severely delayed growth, low uniformity, lethargy, watery diarrhea, delayed feed consumption, and a decreased conversion rate. Chicken astrovir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
71
2
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(84 citation statements)
references
References 45 publications
5
71
2
6
Order By: Relevance
“…In a subsequent study, however, these authors (Pantin-Jackwood et al, 2008) reported ARVs in 62.80% of the chicken flocks and 45.50% of the turkey flocks tested. Previous studies have reported the presence of ARV in intestinal/faecal samples of broiler chickens (Koo et al, 2013;Mettifogo et al, 2014) although most of these studies indicated low prevalence of ARV as compared to other enteric viruses.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a subsequent study, however, these authors (Pantin-Jackwood et al, 2008) reported ARVs in 62.80% of the chicken flocks and 45.50% of the turkey flocks tested. Previous studies have reported the presence of ARV in intestinal/faecal samples of broiler chickens (Koo et al, 2013;Mettifogo et al, 2014) although most of these studies indicated low prevalence of ARV as compared to other enteric viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Several pathogens such as avian rotavirus, astrovirus, reovirus, coronavirus, adenovirus, Salmonella, Escherichia coli, Enterococcus, and Eimeria spp. have been detected either alone or in different combinations from broiler chickens and turkey flocks afflicted with enteritis (Barnes et al, 2000;Jindal et al, 2010;Pantin-Jackwood et al, 2007, 2008Day and Zsak, 2013;Koo et al, 2013;Mettifogo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations